Utiliser les propriétés algébriques de la fonction exponentielle pour transformer une expression Exercice

Montrer que \(\displaystyle{\forall x \in \mathbb{R}}\), \(\displaystyle{\dfrac{e^{x}}{e^{x}+1}=\dfrac{1}{1+e^{-x}}}\).

Montrer que \(\displaystyle{\forall x \in \mathbb{R}}\), \(\displaystyle{\dfrac{e^{2x}}{e^{2x}+e^{x}}=\dfrac{1}{1+e^{-x}}}\).

Montrer que \(\displaystyle{\forall x \in \mathbb{R}}\), \(\displaystyle{\dfrac{e^{-x}}{e^{x}+1}=\dfrac{e^{-2x}}{1+e^{-x}}}\).

Montrer que \(\displaystyle{\forall x \in \mathbb{R}}\), \(\displaystyle{\dfrac{1+e^{x}}{1-e^{-x}}=\dfrac{1+e^{-x}}{e^{-x}-e^{-2x}}}\).

Montrer que \(\displaystyle{\forall x \in \mathbb{R}}\), \(\displaystyle{\dfrac{e^{x}+1}{e^{x}-1}=\dfrac{1+e^{-x}}{1-e^{-x}}}\).

Montrer que \(\displaystyle{\forall x \in \mathbb{R}}\), \(\displaystyle{\dfrac{e^{x}-e^{-x}}{e^{x}+e^{-x}}=\dfrac{1-e^{-2x}}{1+e^{-2x}}}\).

Montrer que \(\displaystyle{\forall x \in \mathbb{R}}\), \(\displaystyle{\dfrac{e^{2x}-1}{e^{2x}+1}=\dfrac{1-e^{-2x}}{1+e^{-2x}}}\).

énoncé suivant